Value addition of products from finger millet (Eleusine coracana) - Sharma, Daisy; Yamer , Padi (Journal of Postharvest Technology, 2022)
The present study was undertaken to develop value added products from Finger millet (Eleusine coracana) and to estimate their nutritive  values. Finger millet is a nutrient dense and inexpensive cereal cultivated in India but, is highly overlooked and underutilised due to lack of  awareness. Therefore, the objective of this research study was to incorporate finger millet in five different products: biscuits, muffins, crackers,  laddoos and chikkis using different levels of incorporation in the form of flour or whole seeds. The other objectives were to conduct  organoleptic evaluation of the products using standard 9-point hedonic scale, followed by calculation of the nutritive value of the products with  highest acceptability scores using the book ‘Nutritive Value of Indian Foods’ by National Institute of Nutrition, Hyderabad, and comparing it  with their respective control products. The results showed that the products incorporated with Finger millet had higher acceptability score and  nutrition composition in terms of calcium, phosphorus, iron and fibre compared to the control products. Therefore, value addition of products  with finger millet is a fruitful endeavour to improve the flavour, texture, appearance and nutrition of the existing food products in the market,  which can benefit the common population as well as the diseased. Further studies can also be done to develop value added novel food  products from finger millet.
Keywords: Finger millet; value addition; food products; acceptability score; nutritive value